A review of durability improvement in concrete due to bacterial inclusions - Bandlamudi, Radha Kiranmaye; Kar, Arkamitra; Ray Dutta, Jayati (Frontiers in Built Environment, 2023)
Since the invention of industrially produced Portland cement in the nineteenth century, concrete has been the world's most frequently used construction material. Because of the significant CO2 emissions produced during cement manufacture and concrete maintenance and repair costs, sustainably improving concrete durability has become a topic of concern. Bacterial self-healing is a unique method that uses CaCO3 precipitation to repair cracks in concrete, thereby improving the structure's durability. This review highlights the effect of bacterial treatment on concrete durability. The permeation properties, water absorption, and mechanical properties are assessed. Emphasis is laid on the selection of bacteria and bacteria nutrients. The paper overviews the morphological analysis of CaCO3 precipitation by bacterial concrete. Despite the benefits of bacterial technology in concrete, numerous critical concerns remain unresolved. Further investigation on nutrients is required to develop a multi-nutrient system that will improve the efficiency of bacterial precipitation since a good combination of low-cost nutrients would reduce the total cost of bacterial concrete.